قدرة التلاميذ على قراءة النصوص من كتاب حاشية الباجوري في معهد عز الرسالة سيباغا باغا بمندايلينج ناتل - Abdul Lohir Rosyid Nasution; Syaipuddin Ritonga; Zulpina (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study aims to determine the process of teaching reading, students' abilities, identify problems and find solutions in teaching reading with the book "Hashiyat al-Bajuri" at the Ezz al-Risala Institute. This thesis project was carried out at the Izz Al-Risala Institute in Sipapaja, Mendayiling Natal, North Sumatra. The results obtained indicate that the teaching of the book "Hashiyat al-Bajuri" at the Ezz al-Risala Institute in Sabaqa Bagha for grades nine and ten uses the grammar and translation method in addition to the reading aloud method. The reading ability of some third and fourth grade students at the Ezz Al-Risala Institute is good or able to read Arabic texts. Some other students still make mistakes in the reading process, such as mistakes when mentioning shapes or movements, or when reading Arabic texts. In addition, some students are also less fluent in reading Arabic texts. The educational problems in the process of learning to read with the book "Hashiyat Al-Bajuri" one of which is the lack of motivation to learn in students, students also only rely on education in the classroom, difficulty in applying grammar and morphology or giving form to the text they read, teaching aids and teaching materials used are still incomplete, only in the form of teaching aids in the form of highlighters on the board and books used in the learning process. There are still students who do not have books. The solution to the problem is first, while the solution to the problem of lack of student motivation to actively repeat lessons is to always provide motivation to students and not get tired of encouraging students to study hard and always remind them at the end of each lesson. Second, the solution for students who still have difficulty forming each word in the reading process is to create learning activities. The solution to the problem of the lack of teaching aids such as books is to ask the teacher to tell students who do not have the Hasiya Al-Bajuri book to copy part of the book.